(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and aim - The efficacy of dexmedetomidine in decreasing the hemodynamic response to laryngoscopy and intubation has been studied through various routes. However, intravenous administration may cause bradycardia and hypotension, and intranasal administration may be associated with irritation. As drug deposition following nebulization takes place over nasal, buccal, and respiratory mucosa, nebulized dexmedetomidine may be a better alternative to both intravenous and intranasal routes of administration. This study aimed to study the effect of preoperative dexmedetomidine nebulization on the hemodynamic response to laryngoscopy and intubation. Method – A prospective, randomized, double-blinded study where a total of 60 ASA 1 & 2 adult patients of either gender undergoing elective surgeries under general anaesthesia were randomized and given either nebulized dexmedetomidine (1mcg/kg in 3-4 mL NS) or normal saline (4 ml) 30 mins before the induction of anaesthesia. Hemodynamic parameters including heart rate and non-invasive blood pressure were monitored for 10 minutes following laryngoscopy. Result – Following laryngoscopy and intubation, there was a marked and significant increase in heart rate, systolic blood pressure, and mean arterial pressure in the control group compared to the dexmedetomidine group. Conclusion – Preoperative dexmedetomidine nebulization effectively blunts the stress response to laryngoscopy and intubation with no adverse effects.